A case of morphological convergence in sections Stephania and Ciliatae of the liverwort genus Scapania (Scapaniaceae, Marchantiophyta) and an extension of the range of S. metahimalayana to China. (2nd October 2021) - Potemkin, Alexey D.; Vilnet, Anna A.; Bakalin, Vadim A.
ABSTRACT: Introduction: The discovery of Scapania metahimalayana in China highlighted its morphological convergence with S. koponenii, S. pseudojavanica and S. stephanii, belonging to sections Ciliatae and Stephania . This initiated a study of these species with a focus on S. metahimalayana, with the aim of defining the parameters of their morphological variability using morphological and molecular-genetic methods and finding key characters for their differentiation. Methods: A comparison of Scapania metahimalayana, S. koponenii, S. pseudojavanica and S. stephanii was carried out using morphological methods as well as molecular comparison of their ITS1–2/ trn L–F/ rbc L regions. Key results: The separation of Scapania metahimalayana, S. koponenii, S. pseudojavanica and S. stephanii at the species level is confirmed. They are distinct in pigmentation, leaf areolation and surface structure, gemma morphology, perianth mouth structure, and distribution pattern. Morphological and molecular distinctions are tabulated and discussed. A key to species and photomicrographs of S. metahimalayana and S. pseudojavanica are provided. Scapania metahimalayana and S. pseudojavanica are reported for the first time for Yunnan, with S. metahimalayana new to China. The considerable morphological similarity of these four taxa highlights the importance of joint morphological and molecular study for the identification of the infrageneric position of separate species.